Search for the standard model Higgs boson produced in association with a vector boson and decaying into a tau pair in pp collisions at √s = 8 TeV with the ATLAS detector - Aad, Georges; Anders, Christoph; Andrei, George Victor; Baas, Alessandra Edda; Brandt, Oleg; Davygora, Yuriy; Djuvsland, Julia Isabell; Dunford, Monica; Geisler, Manuel Patrice; Giulini, Maddalena; Hanke, Paul; Jongmanns, Jan; et al. (Physical review, 2016)
A search for the standard model Higgs boson produced in association with a vector boson with the decay H→ττ is presented. The data correspond to 20.3 fb−1 of integrated luminosity from proton-proton collisions at √s=8 TeV recorded by the ATLAS experiment at the LHC during 2012. The data agree with the background expectation, and 95% confidence-level upper limits are placed on the cross section of this process. The observed (expected) limit, expressed in terms of the signal strength μ=σ/σSM for mH=125 GeV, is μ<5.6 (3.7). The measured value of the signal strength is μ=2.3±1.6.